Comparison of the Efficacy and Safety of Composite Dental Filling Materials (Nano-Hybrid and Microhybrid): A Double Randomized Clinical Study in Ulan Bator Hospital, Mongolia - Byamba, Daava (Crown: Journal of Dentistry and Health Research, 2024)
Introduction: Composite dental filling materials are widely used for dental restoration because of their aesthetic properties and durability. However, the choice of appropriate filling material is still a matter of debate. The aim of this study was to compare the effectiveness and safety of nano-hybrid and microhybrid composite dental filling materials in a double-blind randomized clinical study at Ulan Bator Hospital, Mongolia. Methods: A total of 60 patients with posterior dental caries were recruited and randomly assigned to receive nano-hybrid or microhybrid composite dental fillings. Patients were clinically evaluated at 6 months, 12 months, and 24 months after patching to assess patch retention, color change, sensitivity, and other complaints. Results: The patch retention rates in the two groups were not significantly different (p>0.05). The color change in the nano-hybrid group was less than that in the microhybrid group (p<0.05). Tooth sensitivity in the two groups was not significantly different (p>0.05). No other complaints were reported by the patient. Conclusion: Nano-hybrid and microhybrid composite dental filling materials have equivalent effectiveness and safety within a period of 24 months. However, nano-hybrid showed less color change compared to microhybrid.